Advance in Gluten-Free Diet - Paolo, Usai-Satta (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The only effective and safe treatment of celiac disease (CD) is a lifelong, strict exclusion of gluten, the so-called gluten-free diet (GFD). As a consequence, strict adherence to the GFD is highly successful and useful to achieve optimal control of symptoms in celiac patients, although, sometimes, nutritional problems can persist despite a strict exclusion of gluten. However, following a strict GFD is not easy and an updated quality assessment of available products is needed for further improvement in gluten-free product development. Similar to CD, GFD is the common dietary approach in non-celiac gluten/wheat sensitivity (NCGWS). NCGWS is another common gluten-related disorder without the diagnostic features of CD. Increasing interest in the association and interaction between irritable bowel syndrome (IBS), functional dyspepsia, and gluten-related disorders can expand our knowledge and understanding of the management of these disorders. In this respect, GFD is considered a therapeutic option in IBS and functional digestive disorders. New insights into the GFD are an exciting scientific challenge for researchers.